2004
DOI: 10.1002/eji.200424892
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection of primary human T cells is determined by tunable thresholds of T cell activation

Abstract: HIV infection of primary human T cells requires T cell activation signals. However, how strength, duration, and quality of TCR signals affect susceptibility of resting human T cells to HIV infection remains poorly understood. We found that the same threshold and duration of antigen signals that lead to optimal T cell activation are required for HIV to progress beyond the level of reverse transcription within resting T cells. Remarkably, sustained cytokine signaling from the IL-2 receptor following TCR triggeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 46 publications
3
52
2
1
Order By: Relevance
“…This seems unlikely, since we examined the cells for early, intermediate, and late activation markers, and we found that the p24 high T cells did not express CD25, HLA-DR, or VLA-1 and only small amounts of CD69. Our results using T cells activated by ECs stand in striking contrast to previous studies, which used similar FACS-based techniques to show that viral replication under other conditions is restricted to highly activated T cells (4,44).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This seems unlikely, since we examined the cells for early, intermediate, and late activation markers, and we found that the p24 high T cells did not express CD25, HLA-DR, or VLA-1 and only small amounts of CD69. Our results using T cells activated by ECs stand in striking contrast to previous studies, which used similar FACS-based techniques to show that viral replication under other conditions is restricted to highly activated T cells (4,44).…”
Section: Discussioncontrasting
confidence: 99%
“…ϩ T cells infected with a vpr-deficient strain (Vpr Ϫ ) that were similarly stimulated underwent multiple cell divisions (44). Vpr can arrest infected cells in G 2 (19,23,49), which is advantageous to the virus because G 2 is the phase of the cell cycle that is optimal for viral replication (18).…”
Section: Ecs Enhance Nefmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains controversial whether HIV-1 is stable in the preintegration state. The recent discovery that subtle stimulation of resting CD4 ϩ T cells allows HIV-1 to overcome these blocks further highlights the need for a more complete understanding of the finely tuned host-virus interaction in resting CD4 ϩ T cells (13,25,38,41,49). In the study presented here, a novel HIV-1 Env-pseudotyped reporter virus was used to study the fate of HIV-1 in resting CD4…”
Section: Resting Cd4mentioning
confidence: 99%
“…Estudios previos han mostrado que las célula s Treg son un objeti vo potencial de la infección por el VIH in vitro (Moreno-Fernandez et al, 2009;Oswald-Richter et al, 2004).…”
Section: Discussionunclassified